(untitled) (Research, Society and Development, 2020)
Through an archaeological study, Foucault discusses the homo oeconomicus, which appears in neoliberal rationality and its power relations. Nowadays, Byung-Chul Han introduces this entrepreneur subject of himself, now under a new guise of the performance subject. In this perspective, the objective of this study was to dialogue with Foucauldian analytics, about the context of biopolitics the historical subject, gradually transformed into homo oeconomicus, and with Han’s analysis, about the context of psychopolitics that shows that this subject is migrating from a discipline society for a performance society. This is a theoretical essay, exploratory with a qualitative approach on the changes in the social, political and economic context that occurred in modern societies of the 21st century, as well as the effects of control technologies on work activities. The results indicate that homo oeconomicus is migrating from a context of biopolitics and is now operating as a performance subject, considering that it is no longer obedience individuals that prevail in this context, but performance individuals. and production. Foucault’s analysis finds limitations nowadays, considering that the author did not fully experience the cyberspace context, as we can identify in the texts written by Han. It appears that even limited to the issues of the 20th century, Foucault became an essential author to deal with the 21st century precisely because it was from the notion of self-entrepreneurship that Han presented what he calls the performance subject. It is concluded that the construction of the 21st century homo oeconomicus goes beyond the physical body and now reaches the human psyche, now subjectified by psychopolitics.